Synthesis of Azepine- or Azocine-Embedded Hexabenzocoronene-Based Nanographenes - Ma, Bin; Xiao, Ming-Jun; Liu, Pi-Jin; An, Peng (Synlett, 2021)
Classical polycyclic aromatic hydrocarbons (PAHs) are a large group of π-conjugated planar structures. To explore more properties of PAHs, new structures have been designed, including some with nonplanar topologies and heteroatom-containing moieties. As important nanographene (NG) units, hexabenzocoronene (HBC) and its derivatives have been intensively researched. Many HBC-based nonplanar NGs have been developed, and heteroatom-doped HBC-based NGs have also been designed and synthesized. Here, we summarize some methods for the synthesis of HBC-based NGs containing a seven- or eight-membered ring, and we discuss our newly synthesized NGs containing embedded azepine or azocine moieties, obtained by a modified synthetic route and a conventional Müllen’s synthetic method, respectively.
Keywords: nanographenes; Diels–Alder reaction; polycyclic aromatic hydrocarbons; hexabenzocoronenes; azepines; azocines